Stress intensity factor for multiple cracks in an inﬁnite plate using hypersingular integral equations - Ghorbanpoor, Razieh; Saberi-Nadjafi, Jafar; Nik Long, Nik Mohd Asri; Erfanian, Majid (Tabriz University, 2020)
In this paper, numerical solutions of multiple cracks problems in an infinite plate are studied. Hypersingular integral equations (hieq) for the cracks are formulated using the complex potential method. For all kernels such as regular or hypersingular kernels, we are using the appropriate quadrature formulas to solve and evaluate the unknown functions numerically . Furthermore, by using this equation the stress intensity factor (SIF) was calculated for crack tips. For two serial cracks (horizontal) and two dissimilar cracks (horizontal and inclined), our numerical results agree with the previous works.